Diesel engine operational and emissions attributes optimization through Taguchi–Grey experiment design: exploring the impact of Al2O3–CNT impregnated orange peel biodiesel–diesel blend fuel - Rai R.; Sahoo R.R. (My University, 2025)
This investigation aimed to enhance the functionality and minimize the harmful emissions of a diesel engine operating under various fuel blends, engine loads, and speeds using both standard techniques and an experimentally designed table (L16 orthogonal array) made with Taguchi's strategy of experimental design. The investigation's design had three governing parameters: fuel type, engine load, and engine speed. Each of these had four levels. The L16 orthogonal array (OA) was used to measure the operational characteristics, such as brake thermal efficiency (BTE) and brake-specific energy consumption (BSEC), as well as the pollution attributes such as brake-specific hydrocarbon (BSHC), brake-specific carbon monoxide (BSCO), and brake-specific nitrogen oxide (BSNO). Signal-to-noise (S/N) ratio and grey analysis were used to find the engine's best operating state so that it could get the most out of its performance while putting out the least amount of pollution. The study showed that engine load was the most influencing parameter for both BTE and BSEC, with contribution ratios of 84.02% and 86.79%, respectively. At 25% engine load, 1000 rpm, and using 20% orange peel biodiesel blended 100 ppm CNT impregnated diesel (OPB20CNT100) fuel (A1–B1–C4), the emissions of BSCO, BSNO, and BSHC were at their lowest levels. Engine load has the most significant impact on emissions. The engine's BSEC reduces by 4.35%, and BSNO emissions increased by 1.24%. BTE, BSCO, and BSHC emissions dropped by 3.1%, 16.96%, and 40.06%, respectively, under the best operating conditions compared to diesel fuel. The investigation demonstrates that the application of Taguchi–Grey optimization technique improves both the operational performance and pollution characteristics of diesel engines. The results showed that biodiesel made from orange peel and impregnated with CNT may be utilized as a sustainable alternative to diesel fuel. © Akadémiai Kiadó, Budapest, Hungary 2024.